2018
DOI: 10.7554/elife.34353
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule assembly governed by tubulin allosteric gain in flexibility and lattice induced fit

Abstract: Microtubules (MTs) are key components of the cytoskeleton and play a central role in cell division and development. MT assembly is known to be associated with a structural change in αβ-tubulin dimers from kinked to straight conformations. How GTP binding renders individual dimers polymerization-competent, however, is still unclear. Here, we have characterized the conformational dynamics and energetics of unassembled tubulin using atomistic molecular dynamics and free energy calculations. Contrary to existing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 71 publications
9
73
0
1
Order By: Relevance
“…TUBB3 is a member of β‐tubulin protein family that heterodimerizes with α‐tubulins to form microtubules. Microtubules are dynamically regulated by polymerization and depolymerization, and their mechanical properties determine their own shape and strength . Besides, βIII‐tubulin protein that is encoded by TUBB3 is upregulated in prostate cancer cells under 3D culture conditions compared to 2D culture condition and elevated expression of βIII‐tubulin may associate with the resistance to microtubule inhibitor docetaxel .…”
Section: Discussionmentioning
confidence: 99%
“…TUBB3 is a member of β‐tubulin protein family that heterodimerizes with α‐tubulins to form microtubules. Microtubules are dynamically regulated by polymerization and depolymerization, and their mechanical properties determine their own shape and strength . Besides, βIII‐tubulin protein that is encoded by TUBB3 is upregulated in prostate cancer cells under 3D culture conditions compared to 2D culture condition and elevated expression of βIII‐tubulin may associate with the resistance to microtubule inhibitor docetaxel .…”
Section: Discussionmentioning
confidence: 99%
“…A conformational change can also be reflected as a change in bending preference of the TC complex relative to the free tubulin. Based on previous MD studies (65,98,99), free tubulin conformation is bent and moves toward a more bent conformation if simulated long enough. To test this hypothesis, we measured the intradimer bending angles of the dimers (Fig.…”
Section: Molecular Dynamics Simulations Reveal Conformational Changesmentioning
confidence: 96%
“…More generally, as stated by the authors (31), analysis of residue contact map and CG bond strength and length is not a measure of the actual binding strength of tubulin dimers; rather, an energy landscape of the lateral and longitudinal interaction of the dimers needs to be calculated. In addition, while a number of other MD studies have contributed toward an atomistic understanding of intradimer bending mechanics (29,30), to our knowledge, previous studies have not examined the free energy of interdimer bending as a function of its nucleotide besides equilibrium trajectory analysis (35,36,41). Finally, previous studies have not estimated the nucleotide dependence of the strength of the longitudinal bond, generally regarded as stronger than the lateral bond.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of microtubule dynamic instability posited that the energetic difference between the two nucleotide states of tubulin in models of microtubule assembly (24,25,(34)(35)(36)(37)(26)(27)(28)(29)(30)(31)(32)(33) is due to differences in the tubulin-tubulin lateral bond strength (25,27,28,31,32,34), tubulin-tubulin longitudinal bond strength (31,32,37), the bending preference or flexibility (24,26,29,30,33,35,36), or indirectly dependent on the lateral bond as a result of nucleotide-dependent bending strain energy (38). At the level of atomic structure, a recent cryo-electron microscopy (cryo-EM) study showed that GDP, GDP-Pi and GTPγS all have compacted lattices (~82 Å) compared to the GMPCPP extended lattice (~ 83.7 Å) (32), consistent with conclusions from earlier cryo-EM studies (37,39).…”
Section: Introductionmentioning
confidence: 99%